YOGA ASANAS SEBAGAI PENUNJANG KONSENTRASI BELAJAR SISWA - Partini, Ni Putu Erlina (Institut Hindu Dharma Negeri Denpasar, 2018)
The concentration of learning plays an important role in the learning process. However, with the development of Science and Technology at this time, the concentration of student learning is not necessarily owned by students. Concentration of mind is a state of learning that requires calm, comfort, someone?s attention in understanding the content of the lesson faced. When a student is not able to focus on the lesson being obtained, students will not be able to concentrate, so students will experience forgetfulness in the subjects being obtained. One training that is considered capable of training mind concentration is yoga. Yoga is part of Hindu philosophy, besides the teachings of yoga listed in the Patanjali Yogasutra are also found in Indian philosophy, Sad Darsana. Both in the teachings of Patanjali and Sad Darsana, both of them fully explain the eight stages of self-control called Astanggayoga. Astanggayoga consists of, yama, nyama, asanas, pranayama, pratyahara, darana, dyana and samadhi in Sarasvati? (2002).